The Relationship between Job Satisfaction and Turnover Intentions among Faculty Members in Ethiopian Higher Education Institutions - Ashenafi Tesfaye Guyo (Indonesian Psychological Research, 2023)
The main objective of this study was to investigate the relationship between job satisfaction and turnover intentions among faculty members in Ethiopian public higher education institutions. A quantitative correlational survey design was employed, and a total of 382 participants were selected through stratified random sampling from five universities of Ethiopian public higher education institutions. To analyze the data, a descriptive approach was used to summarize the findings, while inferential analysis involved correlation and multiple regressions to examine the associations between the variables. The results showed that both intrinsic and extrinsic job satisfaction were significantly associated with turnover intentions. From this finding, it is recommended that the university administration, in collaboration with the Ministry of Education (MoE), takes appropriate measures to ensure that faculty members receive adequate intrinsic and extrinsic job rewards. This will contribute to higher job satisfaction and reduce turnover intentions among academic staff. By addressing these factors, the institutions can retain their valuable workforce.